Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Kopi Instan Merek Kopi Tolaki di Kota Kendari - Nurnaningsi Nurnaningsi; Bahari Bahari; Budiyanto Budiyanto (Universitas Halu Oleo, 2022)
This study aims to analyze the effect of the marketing mix on purchasing decisions for instant coffee of the Kopi Tolaki brand in Kendari city. The sample was determined using the formula Hair et al (2010) so that a sample of 80 respondents who were consumers of Kopi Tolaki was obtained by using accidental sampling technique. Descriptive analysis is used to determine the description of the marketing mix and purchasing decisions according to the perceptions of respondents (consumers), while path analisis is used to determine the direct and indirect effects simultaneously on several independent variables (X), is product (X1), price (X2), location/distribution (X3) and promotion (X4) on the dependent variable, is the purchase decision (Y)T. The result showed that the description of the implementation of the marketing mix and purchasing decisions for Kopi Tolaki in Kendari city according to consumer perceptions was in the high category, meaning that the implementation was quite good. The marketing mix (X) simultaneously has a significant positive effect on purchasing decisions (Y). Partially product (X1), price (X2) and promotion (X4) have a significant positive effect on purchasing decisions with the total direct and indirect effects of each produk (X1) being 8,63%, price (X2) 2,25% and promotion (X4) 7,52%, while the location/distribution (X3) variable has no effect significantly negative on purchasing decisions (Y) with a total direct and indirect effect of -0,06%. Of all the marketing mix research variables, the product (X1) is the variable that has the most significant effect on purchasing decisions (Y).Keywords: mixed marketing; purchasing decisions; path analysis; Kopi Tolaki